DARI PURITAN KE REKONSTRUKSIONIS - Hudaeri, Mohamad (Al Qalam, 2013)
This article tries to understand Islamic reformation movements in the modern era based on two points of views: internal and external aspects. On the one hand, based on the internal aspect, Muslims need to reform their social structure and mental attitudes in arranging their socio-political lift by reforming their religious understanding which is accordance with their developing logics and imagination. In the other hand, based on the external aspect, it is because of the development of 'the economic-political authorities' in this modern era, i.e. a system of nation state, democartion, human ghts and modem capitalism. The changes force Muslims to reform their ways of thinking toward their religious orthodoxy, traditions, and intellectual treasury. To understand reformation movements could not be separated from their historical contexts because the reformation movements are not monolitic. They have various forms and different purposes. However, the religious understanding could not also be separated from the intellectual development and the challenges of life faced by Muslim societies. KeyWords: Islamic Thought Reformation, Islamic Orthodoxy, Islamic Movements